Pengaruh Penerapan Program Pnpm Berkelanjutan Terhadap Kesejahteraah Masyarakat Di Desa Bongo Kecamatan Batudaa Pantai Kabupaten Gorontalo - Alinda Umar Yusuf; Frahmawati Bumulo; Abdulrahim Maruwae; Radia Hafid; Yulianti Toralawe (Jurnal Pendidikan Ekonomi dan Bisnis, 2026)
This study aims to determine the impact of the Sustainable National Community Empowerment Program (PNPM Berkelanjutan) on community welfare in Bongo Village, Batudaa Pantai District, Gorontalo Regency. The research problem is the persistent variation in community welfare levels, which is suspected to be influenced by the program's implementation. The research method used was quantitative with simple linear regression analysis. Data collection techniques included observation, questionnaires, and documentation. The results indicate that the Sustainable PNPM Program has a positive impact on community welfare, contributing 46.1%, while 53.9% is influenced by other variables outside the study. In conclusion, the Sustainable PNPM Program has a significant impact on improving community welfare in this village.